Cross sections of proton capture reactions of Sr isotopes - Galanopoulos, S.; Demetriou, P.; Kokkoris, M.; Kriembardis, G.; Harissopulos, S.; Kunz, R.; Fey, M.; Hammer, J. W.; Gyürky, Gy.; Fülöp, Zs.; Somorjai, E.; Goriely, S. (HNPS Advances in Nuclear Physics, 2019)
Cross section measurements of the proton capture reactions of the 86Sr, 87Sr and 88Sr isotopes were carried out at energies Ep=1.4-5 MeV. At Ep <3.5 MeV an array of 4 HPGe detectors with 100% relative efficiency shielded with BGO scintillators for Compton background suppression was used, whereas at Ep >3.5 MeV, the measurements were performed by means of one HPGe detector of 80% relative efficiency. For the 87Sr(p,7)88Y and 88Sr(p,7)89Y reactions total cross sections ranging from 0.5 μο-5 mb were found. The data analysis of the 86Sr(p,7)87Y reaction is in progress. Cross sections have also been calculated by means of the statistical model code MOST. A very good agreement between the experimental data and the theoretical predictions has been found.